Vaccine hesitancy and post-vaccination adherence to safety measures: A mixed-method study - Inam, Ayesha; Mushtaq, Asia; Zaman, Sahira; Wasif, Samia; Noor, Mah; Khan, Hania Asghar (Frontiers in Public Health, 2023)
Background Despite being recognized as one of the most successful public health measures, vaccination is still considered to be unnecessary and unreliable in the context of the COVID-19 pandemic. The current study utilized a two-pronged approach in analyzing vaccine hesitancy and health behaviors after vaccination by employing a mixed-method design. Phase 1 was aimed at identifying predictors of COVID-19 vaccine hesitancy and acceptance among the Pakistani population using protection motivation theory (PMT), whereas Phase 2 was aimed at exploring the factors related to the vaccination of COVID-19. Method A convenient sample of 1,736 individuals from the vaccine-eligible population (12 years and above) was selected to collect data on vaccine hesitancy and acceptance (Phase 1). Phase 2 of the study explored post-vaccination health behaviors, especially adherence to safety measures for COVID-19, through 23 in-depth interviews with the vaccinated population. Results Multiple regression analyses showed that response cost is a major predictor of vaccine hesitancy (in Phase 1). In terms of the role of demographic variables, the results showed that being male (for severity: B = −0.481; threat appraisal: B = −0.737), old age (B = −0.044), not vaccinated, and not infected with COVID-19 (themselves and family members) are strongly associated with vaccination hesitancy. Results of thematic analysis in Phase 2 revealed that perceived individual experience and insensitivity toward the severity of the disease are strongly associated with a lack of adherence to safety measures of COVID-19. Faith and religious beliefs and reliance on traditional remedies are also key predictors of people's general non-compliance to health behaviors. One interesting aspect that was revealed in the analysis was the general financially and socially destabilized situation in the context of developing countries that contributed to general apathy in the pandemic situation. Conclusion The findings of the current study may help in devising a health model for the public from the developing world to deal with future pandemic situations.